Joy, inspiration, and hope - Kast, Verena, 1943- (Carolyn and Ernest Fay series in analytical psychology ;, 1991)
"Verena Kast makes the case that not only therapists and analysts but also individuals seeking growth in their own lives should give more attention to the elated emotions. Fear of excess (mania) and analytic preoccupation with grief, anxiety, and depression have together caused joy and hope to be shunned as a focus in individuation (the process toward wholeness). Joy answers the human need for elated feeling and meaning in our lives, a need which is often filled in modern society by secularized parodies of religious ecstasy, such as addiction and compulsiveness." "Kast suggests simple techniques for recapturing our joy through development of an autobiography of joy. Using this approach, we can discover what gives us joy personally, how we can best experience joy, and how and why we choke off our joy. By viewing joy, inspiration, and hope as core emotions in our being, we open ourselves to greater wholeness and fuller life."--Book jacket.